Development of an Interactive 3D Animation as a Visual Medium for Depicting Student Life Using Frame by Frame Technique - Asmara, Danu (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study aims to design and produce a short 3D animated film that represents the dynamics of student life, with a focus on reinforcing ethical values, social norms, and courtesy within the academic environment. In the context of today’s digital technology development, 3D animation is considered a highly effective interactive visual learning medium that can capture the attention of younger generations, especially when addressing topics related to character and morality. Traditional methods of delivering such content are often perceived as monotonous and less engaging, prompting the adoption of frame-by-frame animation techniques as an innovative alternative. This technique allows for the creation of smooth and dynamic motion expressions, supporting the emotional and in-depth delivery of messages. The development process includes story planning, character design, animation production, and the evaluation of its effectiveness. The visual production was carried out using Blender version 3.6 for 3D animation creation, and CapCut was used as a post-production editing tool. Evaluation was conducted through surveys, interviews, and observations involving students aged 18–25, analyzed using a mixed-method approach combining quantitative and qualitative data. The results indicate that this animation medium enhances students’ understanding and awareness of the importance of applying ethical values and norms in campus life. Moreover, it is perceived as more attractive and easier to comprehend than traditional learning methods. This study is expected to contribute to the development of educational media based on animation and serve as a reference for the application of visual technologies in higher education